Statistical analysis of the geochemical associations of the subvolcanic formations of the basic structure of Dzhusа pyrite-polymetallic ores deposit, southern Urals mountains - E. I. Yartsev; N. N. Shatagin (Известия высших учебных заведений: Геология и разведка)
Studying of the subvolcanic bodies from the Late Givetian gabbro-diabase complex has revealed heterogeneity of the given group: some bodies have cross-cut ore mineralization, while the others are superimposed by the mineralization. The preliminary petrochemical classification has allowed to reveal 2 groups of dykes differing in composition. In this connection these dykes were typified into apparently pre-ore subvolcanic bodies and a group of post-ore dikes. Statistical processing of the petrochemical data with use of STATISTICA 10 program has aliowed to reveal 2 subgroups of bodies in gabbro-diabase subvolcanic complex and to define the geochemical associations-indicators for each of them.